Effect of gibberellic acid on the growth and yield of groundnut (Arachis hypogaea L.) - Mohammed Hasan; Ismail B.S. (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study was conducted during two different seasons to determine the best concentration of gibberellic acid (GA3) that could result in better growth and higher yield of groundnut (Arachis hypogaea L.). Experiments were conducted during the 2015 dry season and 2016 wet season at the field of the Universiti Kebangsaan Malaysia (UKM), Bangi, Selangor, Malaysia. The purpose of the experiments was to investigate the response of the groundnut plants to four levels of GA3 (0, 50, 100 and 150 mg L−1) as foliar spray at 21 and 42 days after sowing. The treatments were laid out in a randomized complete block design and replicated thrice. The results showed that the treatment of 150 mg L−1 GA3 significantly (p<0.05) increased plant height, number of branches per plant, total dry weight, number of pods per plant, pod yield, 100 seed weight, % shelling, oil content, protein content, seed moisture and germination percentage during the wet and dry seasons. In conclusion, the 150 mg L−1 GA3 concentration is the optimum level required to enhance the growth and yield in groundnuts during the wet and dry seasons.